The Obligation of a Married Daughter to Provide Financial Support for Her Parents - Abdul Hakim; Muhammad Syafiul Umam (Journal of Indonesian Islamic Studies, 2025)
This article aims to explore the legal obligation of daughters to provide financial support (nafaqah) to their parents, both before and after marriage. It also analyzes the responsible parties for parental support when children cannot fulfill this obligation. The study employs a qualitative approach, utilizing a literature review method alongside normative and comparative frameworks. Primary sources include authoritative works in Islamic jurisprudence and relevant scholarly publications. The findings reveal that the obligation to financially support parents is not exclusive to sons but also applies to daughters who possess financial means. If a daughter lacks income or is financially dependent on her husband after marriage, she is not obligated to provide support. However, if she has her earnings—even after marriage—she remains jointly responsible with her male siblings, proportionate to their respective inheritance shares. In cases where the parents have only one daughter who is financially incapable and no other relatives can assist, the responsibility is transferred to the Bayt al-Māl.